Carbon fiber reinforced polymer in drilling: From damage mechanisms to suppression. (15th April 2022) - Gao, Teng; Li, Changhe; Wang, Yiqi; Liu, Xueshu; An, Qinglong; Li, Hao Nan; Zhang, Yanbin; Cao, Huajun; Liu, Bo; Wang, Dazhong; Said, Zafar; Debnath, Sujan; et al.
Abstract: Realizing the integrated manufacturing of components with high specific strength and stiffness is easy using carbon fiber reinforced polymer (CFRP), which has become the preferred material for weight reduction and efficiency enhancement in the aerospace field. Massive connection holes are machined in assembly. However, CFRP is a multiphase material comprising fiber, resin, and interface at the mesoscopic level. Macroscopically, CFRP has the characteristics of heterogeneity, anisotropy, and heat sensitivity, thus easily causing delamination and burr, which limits its application. Only a few systematic analyses and reviews from the aspects of drilling systems, machining conditions, and tools are currently available. This paper presents a systematic scheme of drilling damage suppression from the overall drilling system. First, the formation mechanism of damage at different hole positions, including exit push-out delamination, entrance peel-up delamination, and burr and fiber pull-out, is analyzed. Second, the suppression strategies are systematically reviewed from the following four aspects: drilling techniques and methods, drilling conditions, tool design, and multi-techniques integration. The damage evaluation methods are then summarized from qualitative detection and quantitative characterization, covering destructive and nondestructive testing and delamination factors in different dimensions. Finally, the unique advantages of various suppression strategies are determined, and the research gaps and future popular research directions are prospected.